2013
DOI: 10.1093/toxsci/kft236
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor–Dependent Induction of Liver Fibrosis by Dioxin

Abstract: The contribution of environmental pollutants to liver fibrosis is an important and poorly explored issue. In vitro studies suggest that the environmental pollutant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and other aryl hydrocarbon receptor (AhR) ligands induce several genes that are known to be upregulated during liver fibrosis. Our aim was to determine whether exposure to such pollutants can lead to liver fibrosis and to characterize the mechanisms of action. Mice were treated for 2, 14, or 42 days, once a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 43 publications
10
105
0
Order By: Relevance
“…Development of periportal fibrosis as indicated by excess collagen deposition was determined by qualitative and quantitative assessment of PSR-stained liver sections. In agreement with previous studies (Nault et al, 2015a;Pierre et al, 2014), TCDD treatment significantly increased collagen deposition in the liver (Fig. 6A and B).…”
Section: Par-1 Deficiency Does Not Reduce Tcdd-elicited Hepatotoxicitysupporting
confidence: 93%
See 2 more Smart Citations
“…Development of periportal fibrosis as indicated by excess collagen deposition was determined by qualitative and quantitative assessment of PSR-stained liver sections. In agreement with previous studies (Nault et al, 2015a;Pierre et al, 2014), TCDD treatment significantly increased collagen deposition in the liver (Fig. 6A and B).…”
Section: Par-1 Deficiency Does Not Reduce Tcdd-elicited Hepatotoxicitysupporting
confidence: 93%
“…Recent studies also suggest exposure to environmental contaminants including persistent organic pollutants and organochlorines contributes to metabolic disease development (Cave et al, 2010;Lee et al, 2006Lee et al, , 2007Taylor et al, 2013). For example,2,3,7,, the prototypical aryl hydrocarbon receptor (AhR) ligand, has been shown to contribute to the progression of NAFLD spectrum from simple, reversible steatosis, to steatohepatitis and early signs of fibrosis in mice (Kopec et al, 2013;Nault et al, 2015a;Pierre et al, 2014). Notably, all of these pathologies are elements of the NAFLD spectrum in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…important role in TCDD-elicited fibrosis (Pierre et al, 2014) although the mechanisms involved in AhR-mediated fibrogenesis remain poorly understood.…”
mentioning
confidence: 99%
“…miR-29 family members, including miR-29a, are known to be downregulated in human fibrotic livers (39). Recently, it was reported that activation of AhR induces hepatic fibrosis by directly regulating pro-fibrotic pathways (40). It would be of interest to examine the role of miR-29a-mediated AhR regulation in the development of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%